Ethical Challenges in Collecting and Analysing Biometric Data - Anabela da Conceição Pereira (2nd European Conference on the Impact of AI and Robotics, ECIAIR 2020, 2020)
Working with biometric data involve the discussion of the ethical challenges, but also, of the risks and benefits involved in collecting and analysing such data, their uses and applications. Risks relate with levels of vulnerability concerning the privacy of the mental and physical states of the users (as some technologies are used directly by consumers), and raise questions of whether biometric data has suitable treatment, as well as on the existence of legislative frameworks regulating their uses and applications. This presentation was discussion of the technical, ethical, legal and social implications of the biotechnological (using AI and robotics), which involve the recording, testing and analysis of biometric data, but also on the responsible use of neurotechnological devices directed to the consumer. The main contribution of such discussion was to point out how emergent changes caused by the biotechnological uses in society are affecting the formation of contemporary culture and humans as beings, for some of these objects can also be seen as technological extensions of the human body as well as the cognitive processes.